THE NUMERICAL MODELLING OF TIDES IN A SHALLOW SEMI-ENCLOSED BASIN BY A MODIFIED ELLIPTIC METHOD - Sidjabat, Mulia M. (Marine Research in Indonesia, 1978)
A numerical model which renders possible the numerical solution of the nonlinear tidal equations by obtaining a solution for each individual tidal component is developed. For this purpose, a set of time independent non-linear equations for each tidal constituent is constructed. Each of these sets of equations is interrelated through the non-linear frictional terms, the approximation of which is accomplished by an iterative scheme. The method is tested for several models before it is applied to the real basin (Bight of Abaco). In order to evaluate the model and to construct the boundary conditions along the opening, a series of tidal observations were undertaken. The viability of the method is indicated by the fact that the results of computations using a coefficient of friction r = 0.0034 give good agreement with observations for all components andÂ  overÂ  all stations.